Adenovirus VAI RNA complexes with the 68 000 Mr protein kinase to regulate its autophosphorylation and activity. - Katze, M G (1987)
We have investigated the interaction of VAI RNA with the interferon-induced, double-stranded (ds) RNA-activated protein kinase, P68, both of which regulate protein synthesis in adenovirus-infected cells. Previous work has shown that during infection by the VAI RNA-negative mutant, dl331, both viral and cellular protein synthesis are inhibited due to phosphorylation of the alpha-subunit of the eukaryotic initiation factor, eIF-2, by the P68 protein kinase. Utilizing monoclonal antibodies specific for P68, we demonstrated that the physical levels of P68 in dl331-infected, wild-type Ad2-infected and uninfected cells were all comparable suggesting that the elevated kinase activity detected during mutant infection was not due to increased P68 synthesis. To examine the basis of the increased activity of P68, the protein kinase was purified from infected-cell extracts using the monoclonal antibody. We found that P68 was heavily autophosphorylated during dl331 infection but not during wild-type or mock infection. The extent of autophosphorylation correlated with elevated P68 activity and the loss of the dsRNA requirements to phosphorylate the exogenous substrates, eIF-1 alpha and histones. We also analyzed VAI RNA function in vitro and present evidence that purified VAI RNA can block the autophosphorylation of P68 in the ribosomal salt wash fraction of interferon-treated cells. Finally we suggest VAI RNA functions through a direct interaction with the P68 protein kinase, since we demonstrated that VAI RNA forms a complex with P68 both in vitro and in vivo.